Blockchain, big data and machine learning : trends and applications - Kumar, Neeraj (Computer scientist); Gayathri, N.; Rahman, Md. Arafatur; Balusamy, Balamurugan (Boca Raton, FL : CRC Press, 2020)
"Present book covers new paradigms in Blockchain, big data and machine learning concepts including applications and case studies. It explains dead fusion in realizing the privacy and security of blockchain based data analytic environment. Recent research of security based on big data, blockchain and machine learning has been explained through actual work by practitioners and researchers, including their technical evaluation and comparison with existing technologies. The theoretical background and experimental case studies related to real-time environment are covered as well"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); Big data; Machine learning; COMPUTERS / Machine Theory; COMPUTERS / Computer Engineering; COMPUTERS / Cryptography